Effect of La3+ and Ba2+ substitution on structural and electrical properties of charge ordered Divalent-Doped Sm0.5Ca0.5MnO3 Manganite - AbdulRuhim, Nuraina Hanum; Rajmi, Rozilah; Kamaruzzaman, Muhammad Zulharmi Taqzim; Ibrahim, Norazila Ibrahim; Yaakob, Muhamad Kamil (Universiti Teknologi MARA, Perlis, 2025)
The fascinating characteristics of mixed valence perovskite manganite,such as its colossal magnetoresistance and charge ordering, have drawn a lot of attention. Despite the continuous study, it is still difficult to modify the charge ordering and its structure by A-site substitution. Thus, this study addresses the problem of understanding the effect of A-site substitution with different cations on structural and electrical properties of manganite. Through this study, the solid-state reaction approach was used to synthesize the charge ordered Sm0.5Ca0.5MnO3, Sm0.2La0.3Ca0.5MnO3 and Sm0.5Ca0.2Ba0.3MnO3 manganite. The structural and electrical properties of these materials were investigated. The single-phase, well-crystallized samples were all in an orthorhombic structure with a Pnma space group, according to the X-ray diffraction patterns. La3+ and Ba2+ substituted samples through Rietveld refinement show higher values of unit cell volume, indicating that the substitution at manganite's A-site was successful. According to Fourier transform infrared spectroscopy, the metal-oxygen and Mn-O bonds are visible at the 550 cm−1 and 650 cm−1 bands, respectively. While the fourpoint probe method was used to examine the impact of La3+ and Ba2+ electrical resistivity. Sm0.5Ca0.5MnO3 and Sm0.5Ca0.2Ba0.3MnO3 manganite exhibit insulating properties in a temperature range of 30 K to 300 K, according to electrical resistivity measurements, while Sm0.2La0.3Ca0.5MnO3 exhibits a metal-insulator transition. The magnetoresistance effect is demonstrated by the fact that all samples' resistivity was reduced by adding an external magnetic field of 0.8 T. The suppression of charge-ordered phase in Sm0.2La0.3Ca0.5MnO3 , which is linked to increase in tolerance factor shows significant role and improved the double exchange mechanism. In Sm0.5Ca0.2Ba0.3MnO3 , on the other hand, the weakening of charge-ordered phase is related to the A-site mismatch cation, which has bigger impact than high value of bandwidth and tolerance factor.